A Burst Phase Analysis Technique for High Precision Time Delay Estimation of Frequency Hopping GSM Signals - Götz, Alexander; Rose, Richard; Zorn, Stefan; Fischer, Georg; Weigel, Robert (Asia-Pacific Microwave Conference (APMC), 2011)
In this paper, a novel burst phase analysis technique for high precision time delay estimation of frequency hopping GSM signals is presented. The technique makes use of the increased bandwidth of frequency hopping waveforms and acquires and processes the signals in a coherent way. This way, the actual applicable bandwidth for time delay estimation and localization purposes is increased significantly. In case of E-GSM 900 systems, up to 35 MHz of bandwidth can be used which enables localization of mobile phones in the order of a few meters. The technique is therefore ideally suited for search and rescue applications. The presented method may also be applied to TETRA, DECT, IEEE 802.15.4 (ZigBee) or IEEE 802.15.1 (Bluetooth) signals.
elib2cris::1512001600,goetz2011b
Keywords: GSM; TDOA; Localization; Frequency Hopping

A GSM-Network for Mobile Phone Localization in Disaster Scenarios - Rose, Richard; Meier, Christian; Zorn, Stefan; Götz, Alexander; Weigel, Robert (German Microwave Conference, 2011)
This paper deals with an adjustment and an implementation of a modified GSM-network. This network is necessary to enable the localization of mobile phones, primarily in disaster scenarios. In order to localize a mobile phone it is mandatory, that the phone transmits a signal. As a mobile phone transmits only sporadically without request, it has to be enforced to send a signal to be localized. The enforcing of a transmission is done by means of bringing up an auxiliary GSM-network. The configuration of the GSM-network allows the usage of a special handover procedure with frequency hopping. The implementation of frequency hopping considerably increases the accuracy of applied localization techniques.
elib2cris::1512001600,rose2011

A low cost ultra-wide-band inverted F-Antenna for Cognitive PMSE systems - Stöckle, Andreas; Brendel, Johannes; Rieß, Steffen; Rose, Richard; Fischer, Georg (International Conference on Wireless Information Technology and Systems, 2012)
elib2cris::1512001600,stoeckle2012
Keywords: UWB; IFA; self-complementary; UHF; ultra-wide-band; scanning antenna; SCA

A new Approach on Mobile Phone Localization for Search and Rescue Applications - Zorn, Stefan; Rose, Richard; Götz, Alexander; Weigel, Robert (International conference on indoor positioning and indoor navigation (IPIN), 2010)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. Search and Rescue with modern localization techniques consequently attracts attention from scientific and industrial sides. This paper introduces one part of the I-LOV project, endorsed by the Federal Ministry of Education and Research Germany. Here partners from relief organizations, universities and industry investigate enhancements to disaster handling and victim rescue. One possible option is to take advantage of the fact, that a lot of people own a mobile phone today. Future developments in the area of mobile phone detection by field intensity measurements will be addressed in this paper.
elib2cris::1512001600,zorn2010
Keywords: Clocks; GSM; Phase locked loops; Protocols; Radio frequency; Universal Serial Bus

A new System for Mobile Phone Localization for Search and Rescue Applications - Weigel, Robert; Kölpin, Alexander; Rose, Richard; Zorn, Stefan; Götz, Alexander (Future Security, 2011)
elib2cris::1512001600,weigel2011g

A new technique to improve AoA using dual polarization - Rose, Richard; Zorn, Stefan; Götz, Alexander; Fischer, Georg; Weigel, Robert (European Microwave Conference, 2011)
This paper presents a technique for reducing the AoA measurement error caused by the influence of multipath propagation. This technique can be implemented using two approaches, where either the amplitude or the power of the received signals in the polarization domain can be implicated. After the polarization angle of the LOS signal is derived, the dual polarized antenna configuration has to be computationally rotated by this angle to reduce the influence of multipath components. The simulation results show, that the proposed technique leads to a significant reduction of AoA estimation error originated from a multipath component.
elib2cris::1512001600,rose2011a

An FPGA-Based Fully Synchronized Design of a Bilateral Filter for Real-Time Image Denoising - Gabiger-Rose, Anna; Kube, Matthias; Weigel, Robert; Rose, Richard (IEEE Transactions on Industrial Electronics, 2014)
In this paper, a detailed description of a synchronous field-programmable gate array implementation of a bilateral filter for image processing is given. The bilateral filter is chosen for one unique reason: It reduces noise while preserving details. The design is described on register-transfer level. The distinctive feature of our design concept consists of changing the clock domain in a manner that kernel-based processing is possible, which means the processing of the entire filter window at one pixel clock cycle. This feature of the kernel-based design is supported by the arrangement of the input data into groups so that the internal clock of the design is a multiple of the pixel clock given by a targeted system. Additionally, by the exploitation of the separability and the symmetry of one filter component, the complexity of the design is widely reduced. Combining these features, the bilateral filter is implemented as a highly parallelized pipeline structure with very economical and effective utilization of dedicated resources. Due to the modularity of the filter design, kernels of different sizes can be implemented with low effort using our design and given instructions for scaling. As the original form of the bilateral filter with no approximations or modifications is implemented, the resulting image quality depends on the chosen filter parameters only. Due to the quantization of the filter coefficients, only negligible quality loss is introduced.
elib2cris::1512001600,gabiger-rose2014
Keywords: Bilateral filter; field-programmable gate array (FPGA)

A power saving jamming system for E-GSM900 and DCS1800 cellular phone networks for search and rescue applications - Zorn, Stefan; Maser, Matthias; Götz, Alexander; Rose, Richard; Weigel, Robert (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2011)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. Search and Rescue with modern localization techniques consequently attracts attention from scientific and industrial sides. This paper introduces one part of the I-LOV project, endorsed by the German Federal Ministry of Education and Research. In this project partners from relief organizations, universities and industry investigate enhancements to disaster handling and victim rescue. One possible option is to take advantage of the fact, that a lot of people own a mobile phone today. To locate a person by his or her mobile phone requires to take over the phone by an own Base Transceiver Station (BTS). Jamming all other networks is one option to achieve that. This paper will introduce a new Field Programmable Gate Array (FPGA) based jamming system which consumes little power and disturbs only small parts of the GSM spectrum but reliably cuts all connections between mobile stations (MS) and existing BTS.
elib2cris::1512001600,zorn2011

A power sensor unit for the localization of GSM mobile phones for search and rescue applications - Zorn, Stefan; Bozsik, Gabor Josef; Rose, Richard; Götz, Alexander; Kölpin, Alexander; Weigel, Robert (IEEE Sensors, 2011)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. Recent examples are Haiti 2010 and Fukushima 2011. Search and Rescue with modern localization techniques consequently attracts attention from scientific and industrial sides. This paper introduces a field strength measurement unit, which is part of the I-LOV project1. In this project partners from relief organizations, universities, and industry investigate enhancements in disaster handling and victim rescue. One possible option is to take advantage of the fact that most people own a mobile phone today and take it with them the whole day. To locate a person by his or her mobile phone requires to find the maximum of its radiated field strength. This paper will show a new power sensor unit for GSM signals. The complete design flow from requirements considerations to measurement results will be demonstrated. A dynamic range of 107 dB is only one of the remarkable outcomes.
elib2cris::1512001600,zorn2011a
Keywords: cellular radio; disasters; earthquakes; geomorphology; mobile handsets; sensor placement; statistical analysis; GSM

A Smart Jamming System for UMTS/WCDMA Cellular Phone Networks for Search and Rescue Applications - Zorn, Stefan; Gardill, Markus; Rose, Richard; Götz, Alexander; Weigel, Robert; Kölpin, Alexander (IEEE MTT-S International Microwave Symposium Digest (MTT), 2012, 2012)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. This paper introduces one part of the I-LOV project, endorsed by the German Federal Ministry of Education and Research. In this project partners from relief organizations, universities and industry investigate enhancements to disaster handling and victim rescue. One possible option is to take advantage of the fact, that a lot of people own a mobile phone today. To locate a person by his or her mobile phone requires to take over the phone by an own Base Transceiver Station (BTS). Jamming all other networks is one option to achieve that. This paper will introduce a new Field Programmable Gate Array (FPGA) based jamming system which disturbs only the absolute necessary parts of the WCDMA spectrum but reliably cuts all connections between mobile stations (MS) and existing BTS. The whole system including the signal generator and the front end will be discussed. Also measurement results will be shown.
elib2cris::1512001600,zorn2012
Keywords: GSM; Jamming; Mobile communication; Mobile handsets; Multiaccess communication; Radio frequency; Spread spectrum communication; FPGA

A Spectrum Sensing Network for Cognitive PMSE Systems - Brendel, Johannes; Rieß, Steffen; Stöckle, Andreas; Rummel, Rafael; Rose, Richard; Fischer, Georg (7th Workshop on Software Radios (WSR), 2012)
This paper is about a Spectrum Sensing Network (SSN) which generates an accurate radio environment map (e.g. power over frequency, time, and location) from a given application area. It is intended to be used in combination with cognitive Program Making and Special Events (PMSE) devices (e.g. wireless microphones). It consists of a distributed network of multiple scanning radio receivers and a central data management and storage unit. The parts of the SSN are presented in detail and the advantages and the use cases of such a sensing network structure are outlined.
elib2cris::1512001600,brendel2012

A Time Difference of Arrival System Architecture for GSM Mobile Phone Localization in Search and Rescue Scenarios - Götz, Alexander; Zorn, Stefan; Rose, Richard; Fischer, Georg; Weigel, Robert (Workshop on Positioning, Navigation and Communication (WPNC), 2011)
In this work, a novel architecture of a time difference of arrival based localization system for GSM mobile phones is proposed. The system is well-suited for search and rescue scenarios and comprises receiving stations for GSM signals, a dedicated GSM base station and a radio frequency jamming system for GSM and UMTS signals. The system may be operated in the E-GSM 900 band providing high penetration of the covering debris material and a sufficient overall bandwidth for the time difference of arrival measurements. In this case, the best attainable accuracy of localization is shown to be in the scale of 5 m. The components of the system are described in more detail and possible implementations are proposed. The system may also be applied for the localization of UMTS mobile phones making use of the integrated GSM functionality. The proposed system represents a novel approach for time difference of arrival based localization of mobile phones in search and rescue scenarios.
elib2cris::1512001600,goetz2011
Keywords: GSM; Localization; TDOA

A Wideband Crosscorrelation Technique for High Precision Time Delay Estimation of Frequency Hopping GSM Signals - Götz, Alexander; Rose, Richard; Zorn, Stefan; Fischer, Georg; Weigel, Robert (European Microwave Conference (EuMC), 2011)
In this paper, a novel wideband crosscorrelation technique for high precision time delay estimation of frequency hopping GSM signals is presented. The technique makes use of the increased bandwidth of frequency hopping waveforms and acquires and processes the signals in a coherent way. This way, the actual applicable bandwidth for time delay estimation and localization purposes is increased significantly. In case of E-GSM 900 systems, up to 35 MHz of bandwidth can be used which enables localization of mobile phones in the order of a few meters. The technique is therefore ideally suited for search and rescue applications. The presented method may also be applied to TETRA, DECT, IEEE 802.15.4 (ZigBee) or IEEE 802.15.1 (Bluetooth) signals.
elib2cris::1512001600,goetz2011a
Keywords: GSM; TDOA; Localization; Frequency Hopping

Components and Implementation of a Spectrum Sensing Network for the UHF TV Band - Rieß, Steffen; Brendel, Johannes; Stöckle, Andreas; Rose, Richard; Fischer, Georg (European Microwave Conference (EuMC), 2013)
Spectrum sensing is a major part for the implementation of Cognitive Radio (CR) systems in order to enable dynamic access to the radio frequency spectrum. This paper is about a Spectrum Sensing Network (SSN) which generates an accurate radio environment map (i.e. power over frequency, time and location) in the UHF TV band from 470–870 MHz. It consists of a distributed network of multiple receivers with a broadband antenna and a central data management and storage unit. This contribution focuses on the implementation of such a scanning network which has been setup as universal research platform in several halls at the fairground in Berlin. The SSN itself is part of a complex CR system for Professional Wireless Microphone Systems (PWMS) that is able to provide a dynamic frequency allocation of the connected radio links.
elib2cris::1512001600,riess2013

Concept of an UHF Band Receiver for Spectrum Sensing Applications - Rieß, Steffen; Brendel, Johannes; Stöckle, Andreas; Rose, Richard; Fischer, Georg (IEEE International Symposium on Signals, Systems and Electronics, 2012)
Spectrum sensing is a major part for the implementation of Cognitive Radio (CR) systems in order to enable dynamic access to the radio frequency spectrum. This paper describes a concept for a scanning receiver in the UHF band from 470–870 MHz. Characteristics and design considerations of an Analog and Digital Front-End are given as well as the implementation of a Baseband Processor. This is the central module of the whole receiver and the interface to a higher-level controlling unit connected through a 100 Mbit/s Ethernet link. The control interface for the receiver is similar to a spectrum analyzer and therefore easy integrable in an already existing system. Special attention in the digital part is paid to an IF subsampling approach and the clock generation circuit for the ADC. For the sake of completeness the interface to a configurable antenna and some details to the realization of the power supply are also described. This concept has been implemented in hardware in order to enable investigations for the task of spectrum sensing. Our scanning receiver is part of a complex CR system for Professional Wireless Microphone Systems (PWMS) which should be able to provide a dynamic frequency allocation of the connected radio links.
elib2cris::1512001600,riess2012a

High Precision Local Positioning for Wireless Industry Automation - Zohny, Amr; Ferizi, Alban; Rose, Richard; Weigel, Robert (Embedded World Conference 2011, 2011)
Wireless local positioning systems (WLPS) are currently becoming more entrenched in several elds. Among their most prominent elds of implementations are smart factories and real-time based active mapping for cultural guiding purposes. The development of such systems began with the realization of the positioning core technology. However, as this technology matured, more abstract system aspects materialized as the forthcoming challenge such as infrastructure demands in terms of ranging capabilities, cell requirements regarding bandwidth and most importantly, the energy obligations of the mobile unit. A popular solution to these system demands presents itself as the frequency modulated continuous wave (FMCW) radar technique. The aim of this paper is to discuss its underlying principle, the latest and most recent improvements in this system architecture
elib2cris::1512001600,zohny2011
Keywords: radar; local positioning; radio position measurement; industry automation

Image denoising using bilateral filter with noise-adaptive parameter tuning - Gabiger-Rose, Anna; Kube, Matthias; Schmitt, Peter; Weigel, Robert; Rose, Richard (IECON 2011 - 37th Annual Conference on IEEE Industrial Electronics Society, 2011)
In this work, a novel way to adjust a bilateral filter is presented. The bilateral filter is a combination of domain and range filtering. The domain filter acts as a low-pass filter. The range filter stands for the nonlinear component and plays an important part in edge preserving. Both filtering components can be adjusted by according parameters. Pursuant to our experience and achieved results in terms of the image quality it is more effective to readjust the range filter to the noise level than to cope with the fine tuning of the spatial filter. In this work, we show how the adjustment parameter for the nonlinear range component can be derived from the standard deviation of noise, which allows automatic noise-adaptive adjustment of the filter.
elib2cris::1512001600,gabiger-rose2011b

Noise-adaptive bilateral filtering of projections for Computed Tomography - Gabiger-Rose, Anna; Rose, Richard; Kube, Matthias; Schmitt, Peter; Weigel, Robert (11th International Meeting on Fully Three-Dimensional Image Reconstruction in Radiology and Nuclear Medicine, 2011)
In this work, the image quality enhancement of CT images via filtering of noise in the projections is shown. For denoising, a noise-adaptively adjustable bilateral filter is exerted. The application area of the presented work is nondestructive testing in the industry. Bilateral filtering incorporates the combination of domain and range filtering. The domain filter averages the nearby pixel values and acts thereby as a low-pass filter. The range filter stands for the nonlinear component and plays an important part in edge preserving. These filter components both can be adjusted by corresponding parameters. In this paper, the way is presented how the parameter for the adjustment of the nonlinear component can be derived from the standard deviation of noise. This approach allows to increase the PSNR_dB while retaining the structural similarity MSSIM at a high level. Using the proposed method for the calculation of the range filter parameter an automatic noise-adaptive tuning of the noise filter is possible. Moreover filter tuning is effective for any noise level. Besides the increase of the PSNR_dB and of the MSSIM it is demonstrated, that owing to the bilateral filtering of projections the detectability of the low contrast details in CT images can be improved. As long as the details can be distinguished from noise, it is possible to enhance the contrast resolution of these details due to the bilateral filtering of projections using our proposed filter adjustment.
elib2cris::1512001600,gabiger-rose2011a

Ortung verschütteter Personen anhand ihrer GSM-Mobiltelefone - Rose, Richard; Zorn, Stefan; Götz, Alexander; Weigel, Robert (RadioTecC - Radio Techniques and Technologies for Commercial Communication and Sensing Applications, 2009)
elib2cris::1512001600,rose2009

Ortung von GSM-Mobiltelefonen in Katastrophenszenarien - Götz, Alexander; Rose, Richard; Zorn, Stefan; Weigel, Robert (DGON Navigationskonvent, 2009)
elib2cris::1512001600,goetz2009b

Ortung von GSM Mobiltelefonen zur Vermissten- und Verschuettetensuche - Weigel, Robert; Fischer, Georg; Zorn, Stefan; Rose, Richard; Götz, Alexander (Electrical and Electronic Engineering for Communication Workshop - Entwicklerforum - Fachmesse, 2011)
elib2cris::1512001600,weigel2011c

Performance of Coherent Time Delay Estimation Techniques for Frequency Hopping GSM Signals - Götz, Alexander; Rose, Richard; Zorn, Stefan; Fischer, Georg; Weigel, Robert (Topical Conference on Wireless Sensors and Sensor Networks (RWW / WiSNet), 2012)
In this paper, the performance of coherent time delay estimation techniques for frequency hopping GSM signals is investigated. It is demonstrated that the techniques enable the usage of a substantially higher bandwidth for time delay estimation and localization purposes compared to state-of-the-art techniques. Since resolution and noise performance directly depend on the applied bandwidth of the signals, major improvements can be realized. For E-GSM 900 systems, an overall bandwidth of up to 35 MHz may be used which enables time delay estimation and localization in the scale of a few meters. The coherent time delay estimation techniques are therefore ideally suited for search and rescue applications.
elib2cris::1512001600,goetz2012
Keywords: GSM; TDOA; Localization; Frequency Hopping

The Spectrum Sensing Network: Information Acquisition for the Cognitive PMSE System - Rieß, Steffen; Brendel, Johannes; Stöckle, Andreas; Schröter, Simon; Rose, Richard; Fischer, Georg (Shaker Verlag, 2014)
Accessing the frequency spectrum in a dynamic way has been discussed since several years. The Cognitive Radio (CR) technology was identi ed as enabler in order to use the spectral resources in a more e cient way. However, to guarantee interference free operation between multiple services, spectrum sensing plays a major role of designing such a system. This contribution focuses on the realization of the Spectrum Sensing Network (SSN) that has been developed during a research project in Germany. The SSN involves multiple sensor nodes consisting of a receiver with broadband antenna which are connected to a central controller that is in charge of handling the interfaces and acquired data of the SSN. With this setup it is possible to generate an accurate radio environment map, i.e. power over frequency, time and location, in the UHF frequency range from 470 to 870 MHz. After a short introduction to the system requirements and a project overview, attention is paid to the necessary components of such a distributed sensing grid. The measurement results and the discussion of possible advantages of a SSN show the added value for a CR system. Although, the application and demonstration was based on the improvement of operating conditions for Professional Wireless Microphone Systems (PWMS), the originated eld trial platform is open for reasearch activities related to other CR systems in this frequency range.
elib2cris::1512001600,riess2014
Keywords: PMSE; cognitive radio; spectrum sensing; sensing network; sensing grid; scanning controller; scanning receiver; scanning antenna; radio environment map; data fusion